KAJIAN LITERATUR: PENGGUNAAN BAHASA INDONESIA BAKU SEBAGAI BAHASA AKADEMIK DALAM LINGKUNGAN PERGURUAN TINGGI - Nabila Khairunnisa; Nursahru Ramadhani; Nuril Hasanah Fahma; Nurul Fadhilah Rambe; Sri Ulina Saragih; Ayu Nadira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Standard Indonesian is a language variety that follows established linguistic rules and functions as an academic language in higher education. This study aims to examine the role of standard Indonesian and the factors affecting its use in academic activities. The research employed a literature review method with a descriptive qualitative approach. Data were collected from relevant books and scientific journal articles and analyzed using content analysis. The results show that standard Indonesian plays an important role in supporting academic communication and improving the quality of scientific writing. However, its use still faces challenges, including limited mastery of linguistic rules, the use of non-standard language, and the influence of globalization. Therefore, efforts are needed to strengthen language learning and encourage the consistent use of standard Indonesian in higher education.